The Regulation of Digital Currencies: Shared Experiences from the European and French Law - Arciniega Gil, Luis Roman (2021)
This article addresses the social phenomenon of monetary creation, in the digital world, that has been growing steadily in recent years. The aim is to share the experience of the European and French law in its attempt to determine the legal status of the so-called digital currencies, particularly considering the blockchain as the technical aspect that characterizes their creation and operation. The methodology employed is based on documentary research and analysis of the various legal sources, specifically doctrine, legislation, and case law. The study points out that a regulation of the blockchain as the basic element of cryptocurrencies is essential; a pragmatic approach in the legal qualification of such technical element according to the different uses that can be made of it; as well as the need for a harmonized international agreement considering its cross-border nature to provide legalcertainty to users. In conclusion, digital currencies cannot be qualified as legal tender. However, the fact that they are socially accepted as means of payment, as well as their multifaceted character that lends them to various purposes, make the legal actors to adopt a pragmatic approach framing them legally according to the use that is made of them.